The phylogenetic distribution, anatomy and histology of the post‐cloacal bones and adnexa of geckos. (25th November 2015) - Russell, Anthony P.; Vickaryous, Matthew K.; Bauer, Aaron M.
ABSTRACT: Post‐cloacal bones of gekkotans may be present as a single (medial) pair, two pairs (medial and lateral), or may be lacking. We, herein, demonstrate that the presence of a single medial pair is the ancestral condition for the Gekkota, that the lateral pair is of sporadic occurrence within and between families, except for the Eublepharidae where it is universal, and that absence is also of sporadic occurrence except for the Sphaerodactylidae where it is the ancestral condition. Adult male Tokay geckos ( Gekko gecko ) possess only the medial pair of bones, and these exhibit a regionally‐specific expression of woven, fibrolamellar, and lamellar bone, and an enclosed medullary cavity. Females and small juvenile males lack bony elements but exhibit a conspicuous band of dense connective tissue located about the anterior and lateral margins of the cloacal sacs. As males grow and attain sexual maturity, the medial post‐cloacal bones condense in this band of dense connective tissue, and are thus shown to be dermal ossifications, similar to osteoderms but with muscular associations (although this is also known for crocodylians). Based upon ontogenetic data we set forth a scenario to explain the loss of the medial post‐cloacal bones in various lineages. Differential staining of the cloacal sacs failed to reveal any specialized glandular structures. Investigation of the post‐cloacal spurs shows them to be associated with cellular connective tissue of a type similar to that found in the vicinity of the medial post‐cloacal bones. This suggests that the lateral post‐cloacal bones may also be dermal bones, but histological evidence is needed to corroborate this. J. Morphol. 277:264–277, 2016. © 2015 Wiley Periodicals, Inc.